2021
DOI: 10.3390/admsci11030073
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Management and Entrepreneurship—Introduction

Abstract: Entrepreneurship and innovation are positively related (Zhao 2005; Kyvik 2018; Sant et al [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In addition, they found that introduction of novel products and market innovations appears to be associated with the use of more or less freely accessible information sources (Varis and Littunen, 2010). Carvalho and Madeira (2021) noted that innovation help entrepreneurs exploit change as a business opportunity, apply the idea and make it successful in the market. It is clear that innovation contributes to entrepreneurship development depending on the level of development, forms of innovation, size of the enterprise and environment where enterprises operate or are set up.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they found that introduction of novel products and market innovations appears to be associated with the use of more or less freely accessible information sources (Varis and Littunen, 2010). Carvalho and Madeira (2021) noted that innovation help entrepreneurs exploit change as a business opportunity, apply the idea and make it successful in the market. It is clear that innovation contributes to entrepreneurship development depending on the level of development, forms of innovation, size of the enterprise and environment where enterprises operate or are set up.…”
Section: Introductionmentioning
confidence: 99%